2004
DOI: 10.19030/tlc.v1i11.2007
|View full text |Cite
|
Sign up to set email alerts
|

Why University Teacher Preparation Programs Should Provide A New Set Of Personal Constructions Of Mathematics Through Math Content Courses For Elementary Teachers

Abstract: Teacher preparation programs are in danger of seriously under-preparing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Exposure to course materials, activities and classroom discussions may alter pre-service teachers' beliefs about learning and teaching. Researchers (Tannehill & McPhail, 2014;Sellers, 2004) argued that only when opportunities are created in the teacher education and training programs in which pre-service teachers' perceptions are challenged, their beliefs will change. When pre-service teachers become part of powerful experiences in which they analyze effective practice teaching videos, reflect on their own teaching metaphors and are engaged in problem-solving, they become active problem solvers who will foster constructivist learning environments in their classrooms (Ineson et al, 2015;Sellers, 2004).…”
Section: Journal Of School and Educational Psychologymentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to course materials, activities and classroom discussions may alter pre-service teachers' beliefs about learning and teaching. Researchers (Tannehill & McPhail, 2014;Sellers, 2004) argued that only when opportunities are created in the teacher education and training programs in which pre-service teachers' perceptions are challenged, their beliefs will change. When pre-service teachers become part of powerful experiences in which they analyze effective practice teaching videos, reflect on their own teaching metaphors and are engaged in problem-solving, they become active problem solvers who will foster constructivist learning environments in their classrooms (Ineson et al, 2015;Sellers, 2004).…”
Section: Journal Of School and Educational Psychologymentioning
confidence: 99%
“…Researchers (Tannehill & McPhail, 2014;Sellers, 2004) argued that only when opportunities are created in the teacher education and training programs in which pre-service teachers' perceptions are challenged, their beliefs will change. When pre-service teachers become part of powerful experiences in which they analyze effective practice teaching videos, reflect on their own teaching metaphors and are engaged in problem-solving, they become active problem solvers who will foster constructivist learning environments in their classrooms (Ineson et al, 2015;Sellers, 2004). Yet, however much necessary exposure to student-centred environments may be, is not a guarantee for a change in pre-service teachers' beliefs, as some researchers reported that while certain beliefs became elaborate, others were resistant to change (Borg, 2005).…”
Section: Journal Of School and Educational Psychologymentioning
confidence: 99%
See 1 more Smart Citation